2022
DOI: 10.1037/tra0001050
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between number of trauma types, resilience, and psychological symptoms in ex-military personnel from India.

Abstract: Objective: Traumatic event (TE) types have been shown to relate to adverse psychological outcomes. However, research in this area has relied almost exclusively on linear analysis and has been limited to Western countries with similar cultural values. Addressing these limitations, this study examined (a) presence and nature of relations between number of TE types and psychological outcomes and (b) minimum number of TE types predicting psychological symptoms in a culturally distinct sample of ex-military members… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Asian Indians report traumatic experiences before, during, or after immigration to the U.S., such as natural disasters, witnessing violent death of family members, war/conflict, torture as political prisoners, medical-related traumas, interpersonal traumas (e.g., domestic violence), and racial traumas (Dar & Deb, 2021; Dolan et al, in press; A. R. Gilmoor et al, 2019; Kaduvettoor-Davidson & Inman, 2013; Lee & Lu, 1989; Maji et al, 2021; Pillaia et al, 2015; Rechsteiner et al, 2019).…”
Section: Traumatic Experiences and Posttraumatic Stress Disordermentioning
confidence: 99%
“…Asian Indians report traumatic experiences before, during, or after immigration to the U.S., such as natural disasters, witnessing violent death of family members, war/conflict, torture as political prisoners, medical-related traumas, interpersonal traumas (e.g., domestic violence), and racial traumas (Dar & Deb, 2021; Dolan et al, in press; A. R. Gilmoor et al, 2019; Kaduvettoor-Davidson & Inman, 2013; Lee & Lu, 1989; Maji et al, 2021; Pillaia et al, 2015; Rechsteiner et al, 2019).…”
Section: Traumatic Experiences and Posttraumatic Stress Disordermentioning
confidence: 99%
“…Further, India is one of the nine countries projected to account for more than half of the increase in the global population between 2020 and 2050 (United Nations Department of Economic and Social Affairs Population Division, 2021). Critically, Asian Indians living in India report mental health concerns and stressors (Dolan et al, 2022; Gilmoor et al, 2019). For instance, studies indicate that South Asians (including Asian Indians) report depression and interpersonal violence (Masood et al, 2009), and that the lifetime prevalence of mental health conditions among Asian Indians living in India is ~14% (Murthy, 2017), which is comparable to the worldwide pooled prevalence estimate of common mental health disorders (~13%; Polanczyk et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review of Asian Indians living in India, Gilmoor et al (2019) found the average prevalence rates of PTSD to be as high as ~31% among individuals who experienced natural disasters and ~28% among individuals experiencing abuse. Further, studies have indicated that PTSD is linked to depression (Contractor et al, 2020), distress (Contractor et al, 2014), somatic symptoms (Mushtaq et al, 2006), increased risk of further trauma exposure (Dolan et al, 2022), and increased risk of suicide (A. R. Patel et al, 2021) among Asian Indians living in India.…”
Section: Introductionmentioning
confidence: 99%
“…Limited literature focuses on mental health in the Indian Armed Forces, correlating the type of traumatic event and psychological symptomatology. Still, the prevalence of psychiatric diagnoses in the Indian military is difficult to track (Contractor et al, 2020 ; Dolan et al, 2022 ).…”
mentioning
confidence: 99%